ANALISIS IDENTIFIKASI DAN PENILAIAN RISIKO PADA PROYEK PEMBANGUNAN JALAN DI ATAS SUNGAI (STUDI KASUS JALAN DI ATAS SUNGAI MATI KEC. KUTA, KAB. BADUNG) - I GUSTI AGUNG AYU ISTRI LESTARI; KRISNA KURNIARI; I KADEK DWIRA PUTRA (GANEC SWARA, 2023)
The planning of the Altertantif Road Development Project in Kuta District, Badung Regency, Bali Province was carried out to facilitate access to transportation in the area and to overcome traffic congestion at the Jalan Raya Kuta - Jalan Blambangan intersection. The implementation plan of the Road Construction Project over the Mati River, Kuta District, Badung Regency, Bali Province has various risks that may occur. Risk management is needed to minimize the impact and possibility of risks that will occur in the Road Construction project over the Dead River, Kuta District, Badung Regency, Bali Province. The method used in this research is descriptive qualitative method, namely interviews and brainstorming with competent parties and parties involved in the Road Construction Project over the Dead River, Kuta District, Badung Regency, Bali Province with a total of 25 respondents. Each respondent responds to the likelihood of a risk occurring (likelihood) and responds to the impact/influence that occurs due to the risk (consequences), then will get a risk assessment by multiplying the mode value of the frequency/probability of risk occurrence (likelihood) with the mode value of the influence/impact of risk (consequences). In this study, 34 risk identifications were obtained. These risks include 6 (17.65%) unacceptable risks, 21 (61.76%) undesirable risks, 7 (20.59%) acceptable risks, and 0% or no risks classified as negligible